Cytotaxonomy of five Arabis L. (Brassicaceae) species endemic to Turkey - Şi̇ri̇n, Emrah (Phytotaxa, 2020)
In this study, the karyomorphology of five endemic Arabis taxa (A. alanyensis, A. androsacea, A. aubrietioides, A. davisii, and A. deflexa) was examined. The chromosome number of these species was determined for the first time. As a result of the karyomorphological studies, the chromosome number was determined to be x =8 for all species. Arabis androsacea and A. aubrietioides are tetraploid whereas other species are diploid. Considering the asymmetry indices, we can conclude that all taxa have symmetrical karyotypes. The most common karyotype formulas are 2n = 4x = 32m and 2n = 2x = 14m + 2sm, respectively. Arabis davisii (on the second chromosome pair) and A. deflexa (on the third chromosome pair) are distinguished from others by showing a secondary constriction.